2002
DOI: 10.1524/ract.2002.90.9-11_2002.617
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-chemical effects in the near-field of a final disposal site: role of bromine on the radiolytic processes in NaCl-solutions

Abstract: Chloride / Bromide / Aqueous solution / Pulse radiolysis / Oxidation / Radical anions / EquilibriumSummary. The oxidation of Br − by Cl 2 − is investigated by gamma pulse radiolysis in aqueous solutions of NaCl and NaBr. Depending on the ratio of the concentration of Br − to Cl − , the main product being observed is either Cl 2 − , ClBr − or Br 2 − . The mixed radical anion ClBr − exhibits a broad absorption band at 350 nm with ε 350 = 9300 dm 3 mol −1 cm −1 . The rate constants of the equilibrium Cl 2 − + Br … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 21 publications
(34 reference statements)
1
32
0
Order By: Relevance
“…For the simulation of experiment no. 6 (addition of Br À ) it is necessary to integrate the complex bromide system into the reaction scheme [16,18]. The calculation shows that Br À competes successfully with H 2 for Cl À 2 and OH radicals so that gas evolution can proceed as observed in the experiment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the simulation of experiment no. 6 (addition of Br À ) it is necessary to integrate the complex bromide system into the reaction scheme [16,18]. The calculation shows that Br À competes successfully with H 2 for Cl À 2 and OH radicals so that gas evolution can proceed as observed in the experiment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cl 3 − → Cl 2 + Cl − k = 1.1 × 10 5 s −1[95] ( 6 7 )Cl 2 + H 2 O → HClO + Cl − + H +(68)Similar reactions have been demonstrated for Br, and mixed bromine/chlorine species in weakly acidic solution[95]. The oxidative dissolution of Pu then proceeds as shown[92]:Pu(OH) 4 + HClO → PuO 2 2+ + OH − + Cl − + 2H 2 O (69) Pu(OH) 4 + ClO − → PuO 2 2+ + 2OH − + Cl − + H 2 O (70)The other actinides important for long-term waste storage considerations behave similarly.…”
mentioning
confidence: 99%
“…The radiolysis of high-ionic-strength brine systems has not been extensively studied, but some studies exist (Büppelman, Kim et al 1994;Kelm, Pashalidis, and Kim 1999;Ershov et al 2002). The many components in the brine systems of interest to the WIPP will lead to a relatively complex radiation chemistry and the formation of numerous transients and free radicals.…”
Section: Radiation Chemistry Of Brine Systemsmentioning
confidence: 99%
“…It was also observed that hypochlorite ion generation was negligible when chloride concentrations were smaller than 2 M. Concentrations at a Constant Alpha Activity of 37 GBq/L at pH~12 (Based on Data in Kelm, Pashalidis, and Kim 1999) In the WIPP brine, however, some solutes other than chloride may play a role. Ershov et al (2002) showed that small amounts of bromide in natural brines under radiolysis can give Cl 2 -, ClBr -, and Brradical anions at the radical step, and then mixed halogen molecules and trihalide ions by radical recombination at the molecular step (Ershov et al 2002). The hydrolysis of mixed halogen molecules can then result in the formation of hypobromite (OBr -) (acidic form: (Ershov et al 2002).…”
Section: Radiation Chemistry Of Brine Systemsmentioning
confidence: 99%
See 1 more Smart Citation